A Passion for Scientific Research among Faculty Members Students at the Universities of the Northern Region in Jordan - Ghadeer Salih Khataybeh; Asmaa Suleman Al-Abed Rhmanline; Alia Mohammed Al-Duwairi; Najwa Abdel Hamid Darawsha (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: The current study aimed to reveal the passion for scientific research among graduate students in the universities of the northern region in Jordan. the study sample consisted of 410 faculty members.  Methods: to achieve Objectives of  the study, a descriptive analytical approach was applied. A questionnaire consisting of (41) items distributed to four areas: curiosity, surprise and personal pleasure, students' future aspirations, and students' academic motives. Results: the results of the current study showed that the passion for scientific research among graduate students came  With a medium degree closer to low. the results also showed that there are no statistically significant differences attributed to the variable of sex, academic rank and university type. Conclusions: The study recommended conducting studies dealing with the relationship of the passion for scientific research with other variables, Such as: cognitive competence, emotional intelligence, and professional acumen.